PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN MOTOR SCUTER MATIC YAMAHA DI MAKASSAR - Syaribulan, Syaribulan (Fakultas Ekonomi Universitas Wisnuwardhana, 2017)
ABSTRACTThis study aims to determine whether the variables are simultaneously powerful brand image and variables which have a more dominant influence on purchase decisions scuter matic Yamaha motorcycle in Makassar. The variable in question is corporate image , user image and product image.The research was conducted at PT. Suracojaya Abadi Motor Makassar. The model of research used the method of observation , interviews, questionnaires and literature study carried out systematically on the basis of objective research.The analytical method used is a regression method. Then use the F test to determine the brand image variable (corporate image, user image and product image) is more dominant on purchase decisions scuter matic Yamaha motor and test to determine the brand image variable (corporate image, user image and product image) is more dominant influence on purchase decisions scuter matic Yamaha motor.The results showed that the brand image variable (corporate image, brand image and user image) simultancously influence the purchase decision scuter matic Yamaha motor. From brand image variable (corporate image, user image and product image), product image variable was a more dominant influence on purchase decisions scuter matic Yamaha motor. Thus, the hypothesis can be accepted.Key words : Brand Images, Corporate Image, User Image, Product Image, Buying Decision